Analisis Jalur Hubungan Perceived Ease of Use dan Artificial Intelligence Adoption: Peran Krusial Perceived Usefulness sebagai Mediator - Adeline Putri Kurniawan; F.X. Kurniawan Tjakrawala (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to examine the influence of Perceived Ease of Use on Artificial Intelligence Adoption, with Perceived Usefulness serving as a mediating variable among accounting students in Indonesia. The research employs a quantitative descriptive method, utilizing primary data collected via online questionnaires distributed through a purposive sampling technique to 251 respondents. Data analysis was conducted using the Structural Equation Modeling (SEM) approach with SmartPLS software. The findings indicate that Perceived Ease of Use has a positive and significant effect on both Perceived Usefulness and Artificial Intelligence Adoption. Furthermore, Perceived Usefulness has a positive and significant impact on Artificial Intelligence Adoption and is proven to mediate the relationship between Perceived Ease of Use and Artificial Intelligence Adoption.